Encyclopedia of percussion - Beck, John 1933- (Routledge, Taylor & Francis Group, 2007)
Covering percussion instruments, this book is divided into 4 sections: an alphabetical dictionary of percussion instruments and terms; illustrations of key percussion instruments; longer, individual articles on key members of the percussion family, from Bass Drum to Xylophone; and appendices of terms and symbols and a comprehensive bibliography.